Lithuanian DP book connection with Latvian and Estonian DP in West Europe in 1945-1952 - Remigijus Misiūnas (Knygotyra)
Thousands of Lithuanians, Latvians, and Estonians left their native lands during World War II. They escaped from the second Soviet occupation and spent the post-war years in displaced persons (DP) camps in various West European countries. The living conditions in the camps were very difficult, but the social and cultural activity of the DPs was vibrant. Book publishing was one expression of this activity. Since DPs from the Baltic States lived in the same camps, they had book connections. Several areas of their activity can be discussed.